THE EFFECTIVENESS OF USING SQ4R STRATEGY COMBINED WITH LIVEWORKSHEET IN READING COMPREHENSION AT EFL CLASSROOM - Aszahra, Afnenda Vanola; Fajar, Muh (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2026)
Reading is one of the basic skills in learning English that has to be mastered by the students. Reading becomes the most important activity as a means of consolidating and extending one’s which are knowledge of the language. In the context of teaching reading in EFL classroom, the issue of poor reading comprehension has become a recurring problem. For this reason, a suitable strategy is needed that can help students to improve their reading comprehension achievement. One of the teaching strategies for reading comprehension is SQ4R. The researcher also combines the SQ4R strategy with Liveworksheet. This study aims To investigate the effectiveness of using SQ4R strategy combined with Liveworksheet in reading comprehension at EFL classroom. This research method is quantitative with a quasi-experimental research design. In determining the research sample, this study used a purposive sampling technique. The tenth-grade students of SMKN 3 Jombang were selected to participate in this study. The researcher used tenth-grade TKR 2 as the experimental class and tenth-grade DPIB 2 as the control class. The finding of the significant value 2-tailed of the Mann-Whitney U test is 0.000, lower than 0.05. The findings showed a significant difference between students who were taught by using SQ4R strategy combined with Liveworksheet and those who were not. It means that the alternative hypothesis (Ha) is accepted. In conclusion, the combination of SQ4R strategy and Liveworksheet as learning media significantly affects students' reading comprehension.